Profesoři Hermenegild a Karel Škorpilové působící v Bulharsku 2. část - Ludvík Skružný (Theatrum Historiae)
Karel Shkorpil (1859-1944) lived in Bulgaria for 62 years. There he contributed to the development of the Bulgarian educational system, science, archeology, museum work and the Bulgarian-Czechoslovak cultural relations. Since 1926 he has been an honorary consul of Czechoslovakia in Varna. For almost five decades Karel Shkorpil has been traveling around Bulgaria and collecting materials not only about ancient history but also about its folklore, he is interested in architecture, not only Christian and local, but also Ottoman conquerors; saves endangered monuments from the time of the "yoke" and the emergence of the modern Bulgarian people. The collected materials are exhibited in museum rooms, which appear in the high schools, where these rooms affect the young students. During the war he conducted research, photographed, measured monuments, corrected and supplemented military maps of Bulgaria and the occupied lands in neighboring countries. For six decades he has been thinking about the difficult issues related to the history of Bulgaria and the Balkan countries, following old trade and military routes, including those along which Vladislav III's army reached Varna. Yagelo to win a decisive battle for Christendom and Europe, on November 10, 1944. It focuses on numismatics, sphragistics, paleography, historical demography, geography and iconography. Thanks to the knowledge of these auxiliary historical sciences, he was able to more accurately solve historical issues and show evidence that Pliska is the older center of the country than Veliki Preslav. He published the conclusions of his research on the pages of various journals.